Chemotherapy for 70-Year-old women with breast cancer in Germany: A survey by the German breast group - Barinoff, J.; Traut, A.; Bauerschlag, Dirk O.; Bischoff, J.; Herr, D.; Luebbe, K.; Lueck, H. -J.; Maass, Nicolai; Mundhenke, Christoph; Schmidt, Marcus; Schwedler, K.; Thill, M.; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Aim: Around half of all women in Germany with breast cancer are older than 65 and approximately one third of them is older than 70 years of age. In theory, the preferred therapeutic management of women with breast cancer aged 65 and above corresponds to that formulated for younger patients and complies with the S3 Guidelines and the therapy recommendations formulated by AGO. To study the current therapies used to treat women with breast cancer aged 70 and above in Germany, a survey of the clinics of the German Breast Group (GBG) was done. Method: An online survey was carried out with requests sent to 599 physicians registered as principal investigators in the database of the GBG. The 12-item questionnaire was used to investigate the systematic therapeutic management of 70-year-old patients in different settings. The indication for chemotherapy was taken as a given. Results: In a neoadjuvant setting, 62 % of physicians opted for anthracycline and taxane-based therapy as did 56.6 % of physicians in an adjuvant setting. One third of physicians preferred a taxane-based therapy with the anti-angiogenesis inhibitor bevacizumab as first-line therapy for primary metastatic cancer and after anthracycline-based therapy. Capecitabine (around 30 %) and navelbine (around 20 %) were proposed as second-line neoadjuvant and adjuvant therapies after prior anthracycline- and taxane-based therapy. Conclusion: The chemotherapy regimen prescribed for women with breast cancer aged 70 and above in Germany appears to be relatively standardised and corresponds to the recommendations given in the S3 Guidelines and by the AGO Breast Committee. © Georg Thieme Verlag KG Stuttgart New York.
CRIS-Team Scopus Importer:2022-11-17
Keywords: breast carcinoma; breast malignancy; metastasis